ChemInform Abstract: Synthesis of Amino Heterocycle Aspartyl Protease Inhibitors. Issue 30 (July 2016) - Chambers, Rachel K.; Khan, Tanweer A.; Olsen, David B.; Sleebs, Brad E.
Abstract: Review: [51 refs.